The Drivers of Environmentally Sustainable Hospital Foodservices - Carino, Stefanie; Malekpour, Shirin; Porter, Judi; Collins, Jorja (Frontiers in Nutrition, 2021)
Background Hospital foodservices have the potential to positively contribute to the local food system and planetary healthcare. Understanding the factors contributing to the success of “exemplar hospitals” with environmentally sustainable foodservices gives opportunity to reimagine foodservices and guide strategic planning. The aim of the study was to identify the drivers of sustainable hospital foodservices. Methods For this qualitative multiple case study, purposive sampling was used to identify exemplar hospitals internationally. Semi-structured interviews were conducted with staff with extensive knowledge of their foodservices to explore the drivers of sustainable practices. Relevant documents provided background on the case. These documents and interview data were analysed using framework and thematic analysis. Findings There were 21 participants from 14 hospitals recruited across 9 countries. Sustainable foodservice practices included local and organic food procurement, gardens onsite, vegetarian menus, re-serving unopened portion controlled items, traditional foods and food waste composting. Four themes were identified: initiating drivers, supporting enablers, challenges and influence. Initiating drivers that ‘sparked’ sustainable practices included the values of individuals or the hospital (e.g. community, environmental or religious values), logical solutions to a problem, or government requirements. Enablers that facilitated success included motivated individuals, dedicated personnel, supportive leadership, internal protocols and perceived benefits. External enablers included being part of member organisations, government requirements, and learning from other hospitals. Exemplar hospitals had broader influence including educating the hospital community, supporting other hospitals and influencing government policies/targets. Common challenges were staff resistance and inadequate policy directive. Interpretation These findings examine successful international cases of sustainable hospital foodservices to provide a global overview to assist with strategic planning both within hospitals and governing bodies.